Penerapan Model Cooperative Learning dalam Peningkatan Motivasi dan Keterlibatan Belajar Siswa Madrasah Tsanawiyah Negeri Samarinda - Atika Muliyandari; Rahmatillah Rahmatillah (Itqan: Jurnal Ilmu-ilmu Kependidikan, 2024)
This study focuses on the implementation of the cooperative learning model at Madrasah Tsanawiyah Negeri Samarinda and its impact on enhancing students' motivation and engagement in learning. The research employs both quantitative and qualitative approaches (mix method). Quantitatively, data were collected through measurements of students' motivation and engagement before and after the application of the cooperative learning model. The statistical analyses included descriptive tests, correlation tests, and regression analysis. Qualitatively, interviews with the school principal, teachers, and students, as well as classroom observations, were conducted to gain a deeper understanding of the dynamics of cooperative learning. The results of the study indicate that the cooperative learning model significantly contributes to students' motivation and engagement. Correlation test results show a strong positive relationship between motivation and student engagement (r = 0.68, p < 0.01), while regression analysis indicates that motivation contributes 46% to the increase in student engagement. The qualitative approach supports these findings, revealing that social interactions within cooperative groups enhance students' sense of responsibility, active participation, and confidence in expressing their opinions. Based on these findings, it is recommended that teachers increase the use of the cooperative learning model in daily lessons, particularly in subjects that require interaction and collaboration. Teachers should also be trained to manage group dynamics effectively, ensuring that this model is implemented inclusively, allowing all students to actively participate in the learning process.